Mapping patterns of multiple deprivation in Namibia. Issue 12 (4th December 2017) - Chamboko, Richard; Re, Alessandro; Guvuriro, Sevias
Abstract : Purpose: As an alternative poverty analysis approach, the purpose of this paper is to map the patterns of multiple deprivation in all 13 administrative regions of Namibia using the National Household Income and Expenditure Survey data. Design/methodology/approach: Unsupervised statistical learning methods including the principal component analysis, k-means clustering and bivariate analysis were applied. Findings: The results show that the multiple deprivation approach is a useful alternative in characterising poverty dynamics in the country. Specifically, the mapping shows that other dimensions of poverty such as access to utilities and services among other things are equally useful welfare indicators as they scored higher than income and consumption on discriminant ability. Originality/value: Unpacking the multi-dimensionality aspect of poverty has drawn significant attention from development economists and continues to play a major role in policy formulation for developing countries. The study recommends buttressing of conventional income poverty measures with multiple deprivation approaches for a comprehensive picture on poverty issues.